Hyperacute vestibular syndrome: the role of an acute vertigo service - Bierrum, William; Haider, Salman; Balaratnam, Michelle; Alim-Marvasti, Ali; Chandratheva, Arvind; Simister, Robert; Koohi, Nehzat; Kaski, Diego (Frontiers in Stroke, 2023)
Differentiating between peripheral and central causes of acute vertigo remains a clinical obstacle in the acute setting. Despite the availability of several validated diagnostic algorithms adoption and implementation of these tools is low because most emergency physicians are unfamiliar with them. Embedding an acute vertigo service within the emergency setting may help improve the diagnostic workup of patients presenting with this specific symptomatology and may have significant economic benefits, such as the avoidance of hospital admissions, reduction in unnecessary investigations, and decrease in length of hospital stay. In this work, we present four patients who were referred to the acute vertigo service at University College London Hospital (UCLH) for review. We discuss the indications for and limitations of implementing such a service.